Oscillogram processing algorithm when monitoring cardiac patients' conditions. Issue 1 (May 2021) - Abramov, G V; Abramov, D G; Polovinkin, I P
Abstract: The development of hospital information system requires the improvement of diagnostic and monitoring tools. The tools should provide extensive diagnostics and automatic data processing. In that respect volumetric compression oscillometry is considered a promising technique. However, at present diagnostic findings need to be adjusted by qualified healthcare professionals. The article deals with a process model when measuring arterial blood pressure, compares experimental findings and presents a blood pressure measurement algorithm. The devices designed on the algorithm will allow to conduct an advanced monitoring of patients' conditions without healthcare professionals directly involved. Implementing algorithm-based devices into hospital system will allow to respond to change in patients' conditions urgently.